2022
DOI: 10.3389/fcvm.2022.813550
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental Hypoxia on Hemostasis—A Systematic Review

Abstract: Humans have been ascending to high altitudes for centuries, with a growing number of professional- and leisure-related sojourns occurring in this millennium. A multitude of scientific reports on hemostatic disorders at high altitude suggest that hypoxia is an independent risk factor. However, no systematic analysis of the influence of environmental hypoxia on coagulation, fibrinolysis and platelet function has been performed. To fill this gap, we performed a systematic literature review, including only the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Currently, real-world research does not support the hypothesis that roxadustat leads to increased thrombosis or increased platelet count. 24,25 It is currently unclear whether HIF-PHI increases the risk of thrombotic events in patients infected with coronavirus. However, in the process of correcting anaemia, it is important to control Hb levels within an appropriate range while avoiding sharp fluctuations in Hb levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, real-world research does not support the hypothesis that roxadustat leads to increased thrombosis or increased platelet count. 24,25 It is currently unclear whether HIF-PHI increases the risk of thrombotic events in patients infected with coronavirus. However, in the process of correcting anaemia, it is important to control Hb levels within an appropriate range while avoiding sharp fluctuations in Hb levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia itself promotes thrombosis, and the HIF system can be activated under conditions that promote thrombosis. Currently, real‐world research does not support the hypothesis that roxadustat leads to increased thrombosis or increased platelet count 24,25 . It is currently unclear whether HIF‐PHI increases the risk of thrombotic events in patients infected with coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypoxia itself is thrombogenic, 97 , 98 and the HIF system can be activated in prothrombotic conditions 99 . Nevertheless, studies performed at high altitudes do not seem to support increased thrombogenicity 100 or increased platelet count 101 . A metanalysis of 30 studies ( n =13,146) showed a higher risk for thrombotic events when using HIF-PHIs than placebo or ESAs 46 .…”
Section: Major Adverse Cardiovascular Events and Thrombotic Riskmentioning
confidence: 99%
“…However, current CRRT prescription in high altitude is largely based on physicians' experiences because CRRT in high altitude may have different adverse and curative effects on AKI from that in low altitude. On the one hand, previous studies found that long-term environmental hypoxia was an independent factor in coagulation dysfunction, hemostatic disorders and thrombocytopenia at high altitude [12][13][14]. Su cient use of anticoagulants in CRRT, which is required to prevent circuit clotting to maintain lter performance, is more likely to increase the bleeding risks and other adverse events in high altitude [1,7].…”
Section: Introductionmentioning
confidence: 99%